Religion, marketing and market: An adjustment in the language of faith. (2010)
The present work if considers to make an analysis of social categories that the first sight does not have proximity, in the truth, can, also, seem antagonistic. One is about the relations between Religion, Marketing and Market. The theoretical reference it is a Social Sciences, however, considers the Religion, in its institutional expression –the church– as a social enterprise, a company of the modern times. Search to demonstrate that, to adhere to the modern world, shaped for the idea of competition and consumption of the capitalist society, the religion reorganized its language to take care of the requirements of these times, already considered post-modernity. This is analysis is made from the Brazilian case, that, as many country of the Latin America, accommodates in its social groups the most recent expressions of the Christian religion, in special, the evangelicals groups, that proliferates the peripheries of the greats cities of this American continent.